ANALISIS EKONOMI USAHATANI SAYURAN ORIENTAL DENGAN SISTEM HIDROPONIK NFT TANPA NAUNGAN GREENHOUSE - Rizkia Intan Athifa; Andjar Astuti; Aris Supriyo Wibowo (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
The increases of demand for vegetables with more hygienic criteria is getting higher. One of the hydroponic vegetables business actor in South Tangerang City is Hydroponic Koe Garden CV Kelapa Agro Lestari which focuses commodity of oriental vegetables with hydroponic method (Nutrient Film Technique) and without shade of greenhouse in hydroponic cultivation process. The aim of this research are analyzing the profit obtained from oriental vegetables farming and measuring the efficiency level of oriental vegetables farming with NFT hydroponic system without greenhouse shade based on R/C ratio on Hydroponic Koe Garden in Cipayung Village, South Tangerang City, Banten Province. This research was conducted from May to July 2018. The type of this research is quantitative descriptive research. Data analysis method used in this research is the cost structure analysis, profit and efficiency analysis of farming based on R/C ratio. The results of the research showed that although Hydroponic Koe Garden CV Kelapa Agro Lestari producing the same types of vegetables with conventional vegetables such as water spinach, caysim and pakcoy, the business remain profitable and efficient. Based on R/C ratio analysis of hydroponic oriental vegetables in Hydroponic Koe Garden are efficient to run (R/C ratio > 1). The R/C rasio for water spinach, caysim and pakcoy commodity are1,17, 1,07 and 1,22 respectively. Hydroponic pakcoy commodity is the most efficient and profitable commodity to run.